Problemas da teoria das fontes do direito à luz da ideia de direito como integridade de Ronald Dworkin - Ommati, José Emílio Medauar (2020)
This paper highlights the problems of the theory of the sources of law considering that law is a collective enterprise and an interpretative social practice, as presented by Ronald Dworkin. Thus, the paper shows that the theory of the sources of law starts from the positivist assumption that law would be a mere matter of fact, from the existence of a rule of recognition, suffering, at this point, from what Dworkin calls semantic sting. Removing the semantic sting, it is possibly understanding law as an interpretative concept, incompatible with a sources of law theory that intends to discovery, beforehand and in a univocal way, what is the valid law.